Assessment of the fragmented QRS relative frequency and its predictive value in patients with pulmonary embolism - Mohammad Reza Dehghani; Mansoureh Baradaran; Alireza Rostamzadeh; Sima Masudi; Amin Aghamiri; Reza Hajizadeh (Babol University of Medical Sciences, 2025)
Background: Acute pulmonary embolism can quickly cause hemodynamic collapse and death. Recent studies have shown that different characteristics of electrocardiogram (ECG) can be used to predict the prognosis of patients. This study aimed to investigate the relative frequency of fragmented QRS in the ECG of patients with pulmonary embolism and its prognostic value. Methods: This study was conducted retrospectively. The files of 106 patients hospitalized with a diagnosis of pulmonary embolism from January 2016 to the end of March 2020 were selected and reviewed. The findings of the ECG, including the ST elevation in V1-V4 leads with and without T invention, right axis deviation, right bundle branch block (RBBB), PR, QRS, QTc intervals, type of treatment (thrombolysis or embolectomy), cardiogenic shock, mortality were collected. Finally, the data were recorded and analyzed in SPSS software Version 16. Results: Hypertension, dyslipidemia, and diabetes mellitus were the most frequent risk factors among the patients. The relative frequency of fragmented QRS, at least in one lead, was 26.2%. The use of thrombolysis, mechanical ventilation, embolectomy, cardiogenic shock, and in-hospital death was significantly higher among patients who had fragmented QRS (P<0.001). CTNI was significantly higher in patients with fragmented QRS (P=0.001). In patients with fragmented QRS large vessels, involvement was significantly higher. Conclusion: This study showed that the presence of fragmented QRS in the ECG of acute embolism patients has a significant relationship with cardiogenic shock, hospital mortality, and the need for advanced treatment methods such as intubation, embolectomy, and the use of thrombolysis.